Henckelia collegii-sancti-thomasii: a new species of Henckelia (Gesneriaceae) from Northeastern India - Borah, Dipankar; Taram, Momang; Joe, Alfred; Neelamkavil, Sandhya Vincent (Phytotaxa, 2019)
Henckelia collegii-sancti-thomasii, a new species of Henckelia is described here from Nirijuli, Papum Pare district of Arunachal Pradesh, northeastern India. Detailed description, its habitat and ecology along with color photographs are provided.